Corrosion behavior of NiCrAlY coatings under alternating salt spray and high temperature environment - DING Hang; WU Xudong; HUANG Ting; XIN Lipo; FU Yong; XIE Yun (Journal of Aeronautical Materials)
Corrosion problem resulting from alternating ambient salt spray and high temperature oxidation poses a great threat to the safe service of aircraft engine during frequent start-stop in marine environment. In the present study，Ni25Cr5AlY coating is prepared on top of GH4169 superalloy substrate by direct-current（DC） magnetron sputtering. Corrosion behavior of the Ni25Cr5AlY coating is systematically studied by designing three different test conditions： high temperature oxidation at 1000 ℃，ambient salt spray，and alternating ambient salt spray and high temperature oxidation. The phase constitution and morphology of the corrosion products are analyzed by X-ray diffraction（XRD） and scanning electron microscopy（SEM）. The results indicate that after 168 h oxidation at 1000 ℃，the coating forms a dense and continuous Al2O3 scale which resists well against the oxidizing environment，while the coating suffers from pitting locally after 168 h salt spray test. After 168 h exposure to alternating ambient salt spray and high temperature oxidation test，the Al2O3 scale formed on the coating is damaged owing to the chlorine induced active oxidation mechanism，eventually resulting in Cr2O3 scale formation. In addition，the Cr2O3 scale is porous and cracks locally，which causes accelerated corrosion of the coating and internal oxidation of the coating and substrate. The corrosion degradation of the coating is accelerated under the synergistic effect of salt spray and high temperature oxidation. The GH4169 superalloy without the coating experiences severe scale spallation after 168 h exposure to the alternating test，featured by forming a poorly protective NiO scale with prevalent internal oxidation.